(untitled) (The Conference Hub, 2025)
This article explores the scientific importance of integrating information technologies into the process of developing aesthetic education. It highlights how digital tools and multimedia platforms can enhance learners’ perception of beauty, art, and cultural values. The paper analyzes the role of virtual resources, interactive environments, and visual-audio content in fostering students’ aesthetic sense and creativity. The findings emphasize that modern technology, when applied pedagogically, can significantly contribute to the formation of aesthetic awareness and artistic thinking in educational settings.